Carcass wrote:
If \(x > 0\) and \(2x-1=\frac{1}{2x+1}\), then \(x=\)
A. \(\frac{1}{2}\)
B. \(\frac{\sqrt{2}}{2}\)
C. \(1\)
D. \(\sqrt{2}\)
E. \(\sqrt{2} + 1\)
Given: \(2x-1=\frac{1}{2x+1}\)
Multiply both sides by \(2x+1\) to get: \((2x-1)(2x+1)=1\)
Expand and simplify to get: \(4x^2-1=1\)
Add 1 to both sides to get: \(4x^2=2\)
Divide both sides by 4 to get: \(x^2=\frac{2}{4}\)
Simplify to get: \(x^2=\frac{1}{2}\)
Since we're told \(x > 0\), we know that \(x = \sqrt{{\frac{1}{2}}}\)
= (√1)/(√2)
= 1/(√2)
= (√2)/2
Answer: B